The family's Social Role in rehabilitating the behavior of the disabled individuals - محمد , أسامة; عاقل, مجد (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aims at identifying the role of family in the rehabilitation of the handicapped child, as well asidentifying some variables that have much to do with modifying the behavior of the handicapped child.The analytical descriptive approach is going to be used in this research.The main method used in this research is the questionnaire. The main findings: The family has an average or mediocre role in the rehabilitation process of the socially disabled, The lower the degree of disability, the lower the proportion of beneficiaries of social rehabilitation, low educational level among mothers and fathers of disabled individuals, Most of the families from which the handicapped are of low or middle income